Status of water resources in Nepal and existing use in Irrigation - Poudel, Govinda Prasad (Journal of Innovations in Engineering Education, 2019)
The surface water available in the country is estimated to be about 225 billion cu.m per annum, out of which only 15 billion cu.m per annum is in use. In addition to surface water, a large volume of water is available in the shallow and deep aquifers which are estimated to be 8.8 billion cu.m annually which can be used for irrigation and domestic water supplies. At present less than 50% of the cultivated area has intermittent irrigation facilities and less than 20% of cultivated area has year round irrigation.Nepal’s economy is largely based on agriculture however, Nepalese agriculture is mainly rain fed and agriculture production in both rain fed as well as irrigated areas are being badly affected due to droughts, flooding, erratic rainfall, and other extreme weather events. It is necessary that the modern agriculture practice with the help of year round irrigation we can increase the GDP and provides greater employment opportunities and ultimately we can do sustainable agriculture development. Present water consumption rate is less than 8% of the country’s water potential for irrigation sector. This water consumption rate is very low for our country. This consumption rate can be increase by making a comprehensive study and implementation plan by making multipurpose reservoir type irrigation project for maximum use of available water resources. Year round irrigation scheme also become great tool to get optimum economic development in agricultural sector and maximum crop yield.